Um olhar sobre o ensino de língua portuguesa a partir das gramáticas virtuais/on-line - Lima, Graziele Thainá Maciel (2022)
In this dissertation, I report my experience as a Portuguese teacher in basic education. Besides that, I reflect on the concept of language and multimodality that is adopted in three virtual grammars: “Nova Gramática On-line” (New On-line Grammar), “Gramática.net.br” (Grammar.net.br) and “Norma culta: língua portuguesa em bom português” (Standard language: Portuguese language in correct Portuguese). The autoethnography, one of the methodological biases adopted in this research, allowed me to broaden my perspective on the teaching process of the Portuguese Language while using Virtual/Online Grammars, that I referred to at the beginning of the COVID-19 pandemic. This study is also based on documental (GIL, 2002), qualitative (ANDRÉ, 2004), and interpretive (MOITA LOPES, 1994) research. Assuming that the perception of history constitutes and affects the perception of the present (MENEZES DE SOUZA, 2011) and that the grammatization concerns the process of instrumentalization of a language based on two technologies: the dictionary and the grammar (AUROUX,1992), the aim of this research is to reflect on the Portuguese teaching process considering the autoethnography report of my experience including such Virtual/On-line Grammars in Portuguese classes. Furthermore, I identified the contents that are presented in these materials and how they are approached, considering the orientations for the teaching of Portuguese stated at BNCC (BRASIL, 2017, 2019). Besides that, I identified the multimodal resources (written, sound, image, movement, video, etc.) that are present in these materials and if they are mentioned during the process of teaching grammar. The investigation was carried out with the purpose of tracing a study on the teaching of grammar in social practice contexts to contemporary students in order to provide them with reflective grammar learning. In this dissertation, I also presented some practical teaching suggestions including the analysis of different ways of understanding the concept of language and multimodality in the grammar teaching process. From the data collected and its analysis, I conclude that multimodality aspects are included in grammar activities but in a superficial way since cyberspace resources are not completely exploited. Elaborating on some activity suggestions allowed me to verify that it is necessary and possible for teachers to understand the teaching of grammar as going beyond the standard language rules, as it is still proposed in most current Portuguese language teaching manuals. It is necessary to teach contemporary students, who live in digital societies, to take into account language from a multimodal perspective, including and exploring images and other resources available in cyberspace, such as gifs, memes, videos, and chats, so that they may reflect on how societies are organized and how they can contribute to reorganizing such societies, ensuring social justice.